RECORD GROUPS FOR THE JACK O'CONNELL COLLECTION (UNDER CONSTRUCTION) - Evelyn Taylor:::Archivist ::: (2025)
When used in conjunction with the Finding Guide, Record Group designation helps the researcher ascertain what items are available, their format, and the subject or topic addressed.